2019
DOI: 10.1016/j.trechm.2019.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Key Issues Hindering a Practical Lithium-Metal Anode

Abstract: Advanced liquid electrolytes can achieve dense Li deposition with a Coulombic efficiency (CE) of approximately 99%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
308
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(313 citation statements)
references
References 49 publications
4
308
1
Order By: Relevance
“…The development of electric vehicles demands Li ion batteries with higher energy density . Among all the possible anode materials for the next generation of batteries, Li metal is regarded as the ultimate choice owing to its ultrahigh specific capacity and negative redox potential . However, its practical application is severely hindered by the problems of uncontrollable dendrite growth, low Coulombic efficiency (CE) and Li metal deactivation during the electrochemical plating and stripping process .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of electric vehicles demands Li ion batteries with higher energy density . Among all the possible anode materials for the next generation of batteries, Li metal is regarded as the ultimate choice owing to its ultrahigh specific capacity and negative redox potential . However, its practical application is severely hindered by the problems of uncontrollable dendrite growth, low Coulombic efficiency (CE) and Li metal deactivation during the electrochemical plating and stripping process .…”
Section: Introductionmentioning
confidence: 99%
“…Among all the possible anode materials for the next generation of batteries, Li metal is regarded as the ultimate choice owing to its ultrahigh specific capacity and negative redox potential . However, its practical application is severely hindered by the problems of uncontrollable dendrite growth, low Coulombic efficiency (CE) and Li metal deactivation during the electrochemical plating and stripping process . Strategies such as electrolyte engineering, artificial solid electrolyte interphase (SEI), structured electrodes, and separator membrane modification, have been demonstrated to be effective in alleviating these issues via regulation of Li ion transport and/or interfacial properties …”
Section: Introductionmentioning
confidence: 99%
“…Though the porosity is certainly higher at 6 than at 1 mA cm −2 , using SAW produces far better deposition behavior. Again, the top view images support this conclusion, with substantial porosity and dendrites in the cell without SAW (Figure 2k,l) and homogeneous “chunked” morphology with SAW (Figure 2p) known to result from homogeneous current distribution during deposition 28…”
mentioning
confidence: 53%
“…Significant advances in characterizations are helping researchers get unprecedentedly close to truly understand the LMB working and failure mechanisms . Nevertheless, basic questions on the Li dendrites and SEI still remain.…”
Section: Figurementioning
confidence: 99%
“…It is suggested that the minimization of SEI formation is necessary when using high-surface-area 3D current collectors.Significant advances in characterizations are helping researchers get unprecedentedly close to truly understand the LMB working and failure mechanisms. [12] Nevertheless, basic questions on the Li dendrites and SEI still remain. For instance, how are the SEI-covering Li dendrites formed and what is the role of SEI during Li dendrite formation?…”
mentioning
confidence: 99%